P13.02 Conventional MRI radiomics in the diagnosis of early- and pseudo-progression. (6th September 2019) - Bani Sadr, A; Eker, O F; Berner, L; Ameli, R; Hermier, M; Barritault, M; Meyronet, D; Guyotat, J; Jouanneau, E; Honnorat, J; Ducray, F; Berthezène, Y
Abstract: BACKGROUND: After radiochemotherapy, 20% to 30% of patients with early worsening MRI experience pseudoprogression (Psp) which is not distinguishable from early progression (EP). We aimed to assess the diagnostic performance and survival predictive ability of radiomics in patients with suspected EP or Psp. MATERIAL AND METHODS: Radiomics features (RF) of 76 patients (53 EP and 23 Psp) retrospectively identified were extracted from conventional MRI based on four volumes-of-interest. Subjects were randomly assigned into training and validation groups. Classification model (EP versus Psp) consisted of a random forest algorithm after univariate filtering. Overall (OS) and progression-free survivals (PFS) were predicted using a semi-supervised principal component analysis and, forecasts were evaluated using C index and integrated Brier scores (IBS). RESULTS: Using 11 RFs, radiomics classified patients with 75.0% and 76.0% accuracy, 81.6% and 94.1% sensitivity, 50.0% and 37.5% specificity, respectively in training and validation phases. Addition of MGMT promoter status improved accuracy to 83% and 79.2% and, specificity to 63.6% and 75%. OS model included 14 RFs and stratified low- and high-risk patients both in the training (hazard ratio (HR), 3.63, p=0.002) and the validation (HR, 3.76, p=0.001) phases. Similarly, PFS model stratified patients during training (HR, 2.58, p=0.005) and validation (HR, 3.58, p=0.004) phases using 5 RF. OS and PFS forecasts had C index of 0.65 and 0.69 and IBS of 0.122 and 0.147, respectively. CONCLUSION: Conventional MRI radiomics has promising diagnostic value, especially when combined with MGMT promoter status, but specificity remains moderate. In addition, our results suggest a potential for predicting OS and PFS.